Activation of invariant natural killer T cells by lipid excess promotes tissue inflammation, insulin resistance, and hepatic steatosis in obese mice - Lan Wu; Vrajesh V. Parekh; Curtis L. Gabriel; Deanna P. Bracy; Pamela A. Marks–Shulman; Robyn A. Tamboli; Sungjune Kim; Yanice Mendez-Fernandez; Gurdyal S. Besra; Jefferson P. Lomenick; Brandon Williams; David H. Wasserman; et al. (2012)
Obesity triggers a low-grade systemic inflammation, which plays an important role in the development of obesity-associated metabolic diseases. In searching for links between lipid accumulation and chronic inflammation, we examined invariant natural killer T (iNKT) cells, a subset of T lymphocytes that react with lipids and regulate inflammatory responses. We show that iNKT cells respond to dietary lipid excess and become activated before or at the time of tissue recruitment of inflammatory leukocytes, and that these cells progressively increase proinflammatory cytokine production in obese mice. Such iNKT cells skew other leukocytes toward proinflammatory cytokine production and induce an imbalanced proinflammatory cytokine environment in multiple tissues. Further, iNKT cell deficiency ameliorates tissue inflammation and provides protection against obesity-induced insulin resistance and hepatic steatosis. Conversely, chronic iNKT cell stimulation using a canonical iNKT cell agonist exacerbates tissue inflammation and obesity-associated metabolic disease. These findings place iNKT cells into the complex network linking lipid excess to inflammation in obesity and suggest new therapeutic avenues for obesity-associated metabolic disorders.